2012
DOI: 10.4304/jltr.3.3.500-507
|View full text |Cite
|
Sign up to set email alerts
|

The Exploring Nature of Methodology in the Current Studies of Language Learning Strategies (LLSs) with Focus on Strategy Inventory for Language Learning (SILL) of Rebecca L. Oxford

Abstract: Abstract-There is not a method abandoned as what it might be called a baby-and-bathwater type reaction.Still all the methods have failed to deliver quit the hoped-for miracles. In this way, methodology alone can never be a solution to find what is searching. Rather it is an aid and suggestion. In addition, in the case of methodology, it is true that we are moving in risky area. Research on the related literature of Language Learning Strategies (LLSs) shows that LLSs has a history of only thirty years that is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The idea of allowing insight into the predictive contribution of per-sonality traits in the context of learning strategies remained disregarded, while the principal results of current studies are based only on simple correlations (Blickle, 1996;Fazeli, 2011b;Kato, 2009;Molaei, 2013;Obralic & Mulalic, 2017). The results reported by Fazeli (2011aFazeli ( , 2012aFazeli ( , 2012bFazeli ( , 2012cFazeli ( , 2012d suggest that only personality traits Conscientiousness and Openness to experience (Intellect) are significant predictors of metacognitive, compensation, social, affective and memory strategies. In addition, he showed that Neuroticism is correlated negatively with the use of Cognitive, Memory, Social and Metacognitive strategies.…”
Section: Personality Type and Language Learning Strategiesmentioning
confidence: 98%
See 1 more Smart Citation
“…The idea of allowing insight into the predictive contribution of per-sonality traits in the context of learning strategies remained disregarded, while the principal results of current studies are based only on simple correlations (Blickle, 1996;Fazeli, 2011b;Kato, 2009;Molaei, 2013;Obralic & Mulalic, 2017). The results reported by Fazeli (2011aFazeli ( , 2012aFazeli ( , 2012bFazeli ( , 2012cFazeli ( , 2012d suggest that only personality traits Conscientiousness and Openness to experience (Intellect) are significant predictors of metacognitive, compensation, social, affective and memory strategies. In addition, he showed that Neuroticism is correlated negatively with the use of Cognitive, Memory, Social and Metacognitive strategies.…”
Section: Personality Type and Language Learning Strategiesmentioning
confidence: 98%
“…In addition, in the research, Myers-Briggs Type Indicators (Myers, Mc-Caulley, Quenk, & Hammer, 1998) are more commonly used, with an emphasis on examining differences in the application of these strategies between personality types (Chen & Hung, 2012;Kayaoglu, 2013). Finally, with the exception of Fazeli (2011aFazeli ( , 2011bFazeli ( , 2012aFazeli ( , 2012bFazeli ( , 2012cFazeli ( , 2012d) regression analysis has not been used in this kind of research so far. The idea of allowing insight into the predictive contribution of per-sonality traits in the context of learning strategies remained disregarded, while the principal results of current studies are based only on simple correlations (Blickle, 1996;Fazeli, 2011b;Kato, 2009;Molaei, 2013;Obralic & Mulalic, 2017).…”
Section: Personality Type and Language Learning Strategiesmentioning
confidence: 99%
“…A level of nuisance might occur when designing the questionnaire in addition to the difficulty of establishing the truthfulness of the responses, which makes it necessary to employ supplementary research tools (Denscombe, 2014). Questionnaires may not reflect the multidimensionality and complexity of language learners' strategy use, as what they reflect may merely be a general illustration of strategy use, which reduces the chance of applying the findings in other environments (Fazeli, 2012). Therefore, these issues were considered by the researcher when choosing MRR, designing the questionnaires and interviews, and interpreting their findings.…”
Section: Rationale For the Questionnairesmentioning
confidence: 99%
“…A self-administered strategy questionnaire design can follow three techniques: using an existing questionnaire precisely; using a modified questionnaire; or developing a new one (Fazeli, 2012). This seems to apply to the questionnaires of Oxford (1990) and Nakatani (2006), in addition to a few other inventories.…”
Section: The Choice Of Questionnaire Designmentioning
confidence: 99%